Acetabular Fracture; its Management and Early Functional Outcome - Muhammad Inam, Hussain Bux Palh, Tauseef Raza, Farhad Alam, Irshad Ahmed, Syed Abdur Rub Abidi, Anam Ullah, Muhammad Adeel, Abdul Akbar (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To evaluate the functional results of open reduction and rigid internal fixation with Reconstruction plates and screws in acetabular fractures Methods: This prospective case series study was carried out on 47 consecutive patients, of either gender and age ranging from 18 to 60 years, who presented with an acetabular fracture within a month of injury at the Orthopedic and Trauma Department of the Medical Teaching Institute Lady Reading Hospital (LRH) in Peshawar, Pakistan, from January 2018 to September 2023. Excluded from the research were patients receiving traction therapy with a trochanteric pin for an open fracture. A non-probabilistic sequential sampling method was applied. Clinical grading followed D’aubigne and Postel’s guidelines, with Matta’s modifications. We measured range of motion, pain, and gait. Results: There were 47 patients in total, ages ranging from 20 to 60, with an average age of 37.52. there were 31 males (66.0%) and 16 females (33%). In 19(40.4%) patients, 5(10.6%) patients have physical violence and 23(48.9%) of the patients, the cause of injury was a road traffic collision. Our study shows that of the patients, 29(61.7%) were involved on the right side and 18(38.3%) on the left. In five (10.6%) of the instances, there was plate loosing. It is shown that 24(51.1%) cases, excellent outcomes were attained, in 15(31.9%) case good, 5(10.6%) cases fair, 3(6.4%) cases poor outcome were attained. Conclusion: According to Matta Grading, all acetabular fractures, including those involving osteoporotic bone, respond excellently to rather well to open reduction and internal fixation using a 3.5-millimeter reconstruction plate and screws. Keywords: Acetabulam, Fracture, Internal fixation, Open Reduction, Rigid Fixation.